Membangun Asas-Asas Peradilan Adat (Studi pada Masyarakat Rejang dan Masyarakat Melayu Bengkulu) - Herlambang Herlambang (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: The idea of the necessary of customary principles should be contemplated seriously in order to anticipate the community development dissanpointing to the judicial process of state. The process is a “security door” to prevent chaos in society. The process can be optional solution for justice seeker from power abuse. This research aims to find the customary trial principles that can be a development of the process as alternative dispute solution. The principles are developed based on discussed model of customary value in Rejang and Malay society in Bengkulu Province. The models are identified empirically supported by anthropology legal method and participatory rural appraisal (PRA). The research shows that the principles of customary trial is developed based on discussion model of Rejang and Malay peoples in Bengkulu based on spirit to achieve agreement. Voluntarily, collegial chairman, and open to public. The place of the trial is determined flexibly, and the trail soon conducte. The trial is conducted based on the evidence and acknowledgement of guilty from offender. The punishment is imposed by considering the violation of the breach and perpetrator condition and victim, and the trial is recorded. The execution is determined by the agreement of both parties. The decision is done in a ritual congratulation and shared prayer after the parties forgive each other. Developing Customary Justice Process Principles (A Study on Rejang and Malay Bengkulu)